Synthesis, structural chemistry, and magnetic properties of Ca3.1Cu0.9RuO6 - Moore, C; Cussen, E; Battle, P (2000)
A polycrystalline sample of Ca3.1Cu0.9RuO6 has been synthesized by standard ceramic techniques. The crystal structure, determined at room temperature by neutron powder diffraction, is a monoclinic distortion of the rhombohedral, pseudo one-dimensional K4CdCl6 structure: space group C2/c, a = 8.99775(4), b = 9.25809(4), c = 6.47424(2) Å, and β=91.629(1)°. The octahedrally coordinated cation site is occupied by Ru and the trigonal prismatic site by 10% Ca, 90% Cu. The latter cations are displaced in an ordered manner away from the center of the prism towards one of the rectangular faces; their coordination number is thus reduced to 4. Neutron diffraction data show the onset of long-range magnetic order at 42(2) K. The data suggest collinear ferrimagnetic ordering of the Cu and Ru spins within each chain and antiferromagnetic interchain coupling. However, a small remanent magnetization of 9x10-3 (μB) per formula unit was measured by SQUID magnetometry at 5 K. The magnetic structure of Ca3.1Cu0.9RuO6 contrasts with the 120°spin structure adopted by other K4CdCl6 phases that do not contain a Jahn-Teller cation; in those cases, the frustration inherent in the lattice is not lifted by a structural distortion. (C) 2000 Academic Press.